A Comparative Analysis of Freedom of Expression in Blue Hair and Aku: A Sartrean Perspective (Scripta : English Department Journal, 2026)
This study analyzes freedom of expression in the song lyrics Blue Hair by TV Girl and the poem Aku by Chairil Anwar through Jean-Paul Sartre's existentialism as elaborated in Existentialism is a Humanism and Stuart Hall's concept of identity and representation. This study employs a descriptive qualitative and comparative literature approach to explore how each work negotiates freedom of expression differently. The analysis reveals that Aku presents an authenticity where the lyrical subject reclaims a socially imposed identity "aku adalah binatang jalang / dari kumpulannya terbuang" as a bold assertion of selfhood and reflecting Sartre's concepts of condemned to be free, anguish, and authentic existence. In contrast, Blue Hair exemplifies a gradual abandonment of authentic self-expression under social pressure, wherein the female character's act of cutting her blue hair symbolizes capitulation to externally defined norms, a condition Sartre identifies as bad faith (mauvaise foi). The comparison demonstrates that freedom of expression is not determined by the intensity of external pressure, but by whether the subject is willing to bear the anguish accompanying full awareness of their freedom. This study contributes to comparative literary research at the intersection of existentialist philosophy and contemporary cultural expression across different languages and historical contexts.